Bounded cohomology via partial differential equations, I - Hartnick, Tobias; Ott, Andreas (Geometry & topology, 2015)
We present a new technique that employs partial differential equations in order to explicitly construct primitives in the continuous bounded cohomology of Lie groups.
Published: 6 January 2016
Gesehen am 21.03.2018